Management by Objective Approach in Nursing Performance Appraisal and its Impact on Quality of Nursing Care - H.S Emamzadeh Ghasemi; Z Vanaky; N Dehghan nayeri; T Salehi; M Salsali; s Faghihzadeh (Tehran University of Medical Sciences, 2007)
Background & Aim: Performance appraisal is one of the most important duties for nursing managers. This will improve the quality of nursing care, and it needs suitable approaches and effective strategies in nursing services. The aim of this study is to determine the impact of performance appraisal using management by objective approach on nursing care quality.Methods & Materials: This was a quasi-experimental and single-blind study that was carried out in two surgical units of an affiliated hospital of Tehran University of Medical Sciences. 80 patients were selected using a randomized sampling. The quality of nursing care were controlled in both experiment and control units before and after the performance appraisal procedure. The procedure was programmed on the basis of management by objective approach for six months in the experiment unit. In the intervention unit, nursing performance appraisal was done three times and in every time head nurse and supervisors participated in giving feedbacks and recommendations for the nurses. At the end of the intervention, quality of nursing care was assessed in both groups blindly. The results were compared and statistically analyzed.Results: Significant difference was found between quality of nursing care in the experiment and control units (P<0.001). Quality of nursing care was significantly different before and after intervention in the experiment unit (P=0.009).Conclusion: Performance appraisal using management by objective approach could increase the quality of nursing care. As a result, using nursing performance appraisal plans according to the basis of MBO could be an effective evaluation way to access the quality of nursing care.